2018
DOI: 10.1111/wrr.12645
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, randomized, single‐blind trial comparing the efficacy of viable cryopreserved placental membrane to human fibroblast‐derived dermal substitute for the treatment of chronic diabetic foot ulcers

Abstract: Randomized controlled clinical trials, the gold standard to determine treatment efficacy against control, have demonstrated advantages of skin substitutes for the treatment of chronic diabetic foot ulcers in comparison to standard of care. However, randomized controlled clinical trials comparing efficacy between two or more skin substitutes are very limited. With growing numbers of new skin substitutes, such studies are essential for treatment and policy-making decisions by wound care providers and payers. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
3
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 27 publications
1
40
3
4
Order By: Relevance
“…These interesting early data need confirming in a further independent RCT. A further study designed to show non‐inferiority of a placental product compared with a human fibroblast‐derived dermal substitute was also found, however, the significance of this finding is unclear given the comparator …”
Section: Recommendationsmentioning
confidence: 98%
See 2 more Smart Citations
“…These interesting early data need confirming in a further independent RCT. A further study designed to show non‐inferiority of a placental product compared with a human fibroblast‐derived dermal substitute was also found, however, the significance of this finding is unclear given the comparator …”
Section: Recommendationsmentioning
confidence: 98%
“…The previous review reported a single study of an amniotic membrane wound graft but commented that the study was of high risk of bias and the conclusions marred by the low rate of healing in the comparator group . In the relatively short period of time since that study, interest in this type of therapy has developed rapidly as shown by the number of new placental‐derived products available and the publication of eight RCTs and a cohort registry study …”
Section: Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These interesting early data therefore need confirming in a further blinded RCT. A further study designed to show noninferiority of a placental product compared with a human fibroblast‐derived dermal substitute was also found; however, the significance of this finding is unclear given the comparator …”
Section: Placental‐derived Productsmentioning
confidence: 97%
“…The previous review reported a single study of a cryopreserved amniotic membrane ulcer graft but commented that the study was at high risk of bias and the conclusions marred by the low rate of healing in the comparator group . In the relatively short period of time since that study, interest in this type of therapy has developed rapidly with the publication of eight RCTs and a cohort registry study …”
Section: Placental‐derived Productsmentioning
confidence: 99%